Pernikahan Beda Agama: Kritik terhadap Argumen Kaum Liberal - Ilham Habibullah; Syamsul Hadi Untung (Universitas Darussalam Gontor, 2018)
Interreligious marriage, especially in Indonesia, could make, a hard polemic in a society. It, In a beginning, was a social issue. But, suddenly, become an intellectual one. This issue, ussualy, comes from intelectual liberal Muslim. They build, in understanding Islamic law, especialy in a interreligious marriage, a contextual approach. It, so that, makes a anthropocentric thought and disobeying a vallue, in Islamic worldview. Hence, I would, as a writter, review reductionic arguments of intelectual liberal Muslim which was justified as freedom of interreligious marriage. I will, to achieve it, refiew their argumen and explain their inconsistent in istinba>t al-ahka>m. The result of this is discovered that interreligious marriage is rulled by Muslim or man in Islam who marries a woman of ahl kitab which is leaned to Islam and good moral. And not in otherwise. And the other result of this is known that marriage of sahabat by woman of ahl al kitab is enticed to Islamic teaching. So that interreligious marriage in Islam is not, as it claimed by the liberal Muslim, an antroposentic view but it is valuable by Islamic worldview.